Experiential learning for groundwater governance in India study data - Meinzen-Dick, Ruth S.; Falk, Thomas; Priyadarshini, Pratiti; Sanil, Richu; Duche, Vishwambhar; ElDidi, Hagar; Kosec, Katrina; Zhang, Wei; Melesse, Mequanint B.; Carrillo, Lucia; Ferguson, Nathaniel; Shastri, Seema Vigneshwar; et al. (International Food Policy Research Institute, 2025)
This data article presents a dataset developed to support a rigorous impact assessment of an experiential learning intervention aimed at enhancing groundwater governance and agricultural water management in rural Indian communities. The intervention combined collective action games, participatory planning tools, and community debriefings to promote behavioral shifts toward sustainable groundwater and surface water management. These tools are designed to support informed decision-making, foster collective action, and strengthen governance of water as a common resource. The impact evaluation follows a randomized control trial design, incorporating baseline and follow-up data from both treatment and control habitations. The dataset encompasses behavioral, social, and institutional variables collected through individual surveys, focus group discussions, and key informant interviews. The intervention and data collection took place in four districts across three Indian states, targeting communities heavily dependent on groundwater. Baseline data were gathered between November 2021 and February 2022, prior to intervention implementation, with follow-up data collected from January to June 2023. The data was collected by local trained enumerators to test the scalability of the approach. Participants were selected through stratified random sampling from a purposively defined sample frame, reflecting groundwater reliance and socioeconomic diversity. The resulting dataset comprises anonymized, structured files detailing demographic, social, agricultural, and water governance information across all study groups. The dataset’s multi-layered structure and detailed documentation enable a wide range of reuse opportunities, including replication of previous analyses, in-depth exploration of behavioral and institutional dynamics, and the advancement of novel methodological approaches in water governance research. It supports diverse research needs spanning cross-regional comparisons and policy evaluations.